Local Trade in the Kingdom of Inderapura in the 17th-18th Century Ce - Sudarman Sudarman; Khairul Amal; Safrudin Halimy K; Rahmawati Rahmawati; Urwatul Wusqo (Universitas Darussalam Gontor, 2020)
AbstractThe research is undertaken with several aims in mind. First, to analyze the local trade conducted in the Kingdom of Inderapura within the 17th-18th century CE. Second, to classify several types of local trade conducted under the patronage of the Kingdom of Inderapura in its effort to ascertain its position as the main patron of commerce on the west coast of Sumatera. One of the policies issued by the king of Inderapura to boost the kingdom’s commerce was not to burden the anchoring merchant ships with paying customs. Here lies the difference between the port of the Kingdom of Inderapura with other ports on the west coast of Sumatera. The article approaches the problem through maritime historical research method. It utilizes the Dutch colonial archives and the Tambo of the Kingdom of Inderapura as the primary sources. Besides that, the research also makes use of related books and scientific journals as secondary sources. To enrich and bring depth to its analysis, the research approaches the research question socio-economically. These sources, then, need to pass the internal and external criticism to validate its reliability. The final steps are synthesis and historiography (putting and arranging those facts into historical writing). The writers discover that there are three types of local trade conducted by the Kingdom of Inderapura along with the 17th-18th century CE: intra-island, inter-ports, and inter-islands trade.Keywords: The Kingdom of Inderapura, Local Trade, VOC, The Kingdom of Aceh Darussalam, The Kingdom of Banten. AbstrakPenelitian ini dilakukan untuk menganalisis tentang pola perniagaan lokal di kerajaan Inderapura pada abad XVII-XVIII M. Hal ini sekaligus untuk mendalami bagaimana pola-pola perniagaan yang dibangun oleh kerajaan Inderapura sehingga kerajaan ini mampu menjadi penopang utama perniagaan di Pantai Barat Sumatera. Salah satu kebijakan yang diterapkan oleh raja Inderapura adalah setiap pedagang yang berlabuh tidak dibebani untuk membayar bea cukai, inilah yang membedakan antara pelabuhan Inderapura dengan pelabuhan yang lainnya di Pantai Barat Sumatera. Penelitian ini menggunakan metode riset sejarah maritim dengan sumber primer berupa arsip kolonial, sumber lokal berupa Tambo kerajaan Inderapura dan sumber sekunder serta pendekatan sosial ekonomi, kemudian sumber-sumber tersebut dikritik dengan melalui kritik internal dan eksternal (memvalidasi akurasi terhadap keaslian sumber), setelah itu dilakukan sintesis dan historigrafi. Dari penelitian ini ditemukan bahwa pola perniagaan yang dipergunakan oleh Kerajaan Inderapura pada abad XVII-XVIII M adalah; pertama, pola perniagaan antar pelabuhan. Kedua, Pola perniagaan antar pulau. Ketiga, pola perniagaan ke pedalaman.Kata Kunci:Kerajaan Inderapura, Perdagangan Lokal, VOC, Kerajaan Aceh Darussalam, Kerajaan Banten.